(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Indian construction industry still follows the primeval work pattern which generates low productivity, poor management in resources, poor waste management, lower quality, high energy consumption, over budgeting and time overrun, etc. Though the abovementioned problems need noteworthy thought and time, increased emphasis must be given to new project management strategies so the Indian growth story doesn’t meet a hasty end. As construction is a physically demanding work environment, site workers are often at risk of long-term injury. This study focuses on the poor ergonomics is likely to result in a loss of worker productivity, higher rates of lost work days through illness, a lack of staff morale and motivation, and increase employee turnover. The ergonomics improvement process systematically identifies ergonomic hazards and puts in place engineering and administrative control measures to quantifiably reduce risk factors. The purpose of this research is providing proper guideline & education about risk and right posture to workers is given by carrying out workshop & training program on site is necessary for workers. Use of software platform like Ansys software for analysis.